AB1246 Reproducible metacarpal joint space thickness measurements using 3D analysis of images acquired with high-resolution peripheral quantitative computed tomography (HR-PQCT). (23rd January 2014) - Barnabe, C.; Buie, H.; Kan, M.; Barr, S.G.; Martin, L.; Boyd, S.K.
Abstract : Background: Joint space narrowing from cartilage loss in RA is associated with irreversible physical disability (1). HR-pQCT, a novel instrument capable ofaccurately and reproducibly imaging bone microstructure at a nominal isotropic voxel dimension of 82 micrometres, shows promise in the longitudinal monitoring of erosion development and repair (2), and may also be the ideal technology for detecting small changes in joint space width over time. Objectives: To assess the reproducibility of a 3D metacarpal joint space thickness measurement with repositioning. Methods: The 2nd and 3rd MCPs of the dominant hand of early rheumatoid arthritis and control subjects were imaged using HR-pQCT (Scanco Medical AG, Brüttisellen, Switzerland). Grayscale data was binarized using the standard patient analysis method to extract bone from the surrounding soft tissue. The periosteal contours are smoothed, and the masks of the smoothed bones are subtracted from the final image to yield a mask of the joint space. The joint space is measured in 3D using the method of "fitting maximal spheres" which provides a distribution of joint space thickness. Results: Seventeen joints were imaged twice, with repositioning between series. The mean joint space width of the 2nd MCP was 1.82 mm (SD 0.20) and of the 3rd MCP was 1.84 mm (SD 0.23). Reproducibility with repositioning was excellent, with overlapping filtered histograms and a root square mean coefficient of variance of 4.8%. Conclusions: We have devised an analytical method to provide precise measurements of metacarpal joint space width, robust to changes in joint position. This method shows excellent potential for analyzing joint space width measurements in longitudinal studies, where repositioning error is of concern. References: Aletaha D, et al. Ann Rheum Dis. 2011 May;70(5):733-9. Finzel S, et al. Ann Rheum Dis. 2011 Sep;70(9):1587-93. Disclosure of Interest: None Declared